Kebijakan Pendidikan Anak Usia Dini (PAUD) Dalam Peningkatan Mutu Pembelajaran di Kabupaten Bogor - Yusi Srihartini; Iim Wasliman; Yosal Iriantara; R Supyan Sauri (Reslaj : Religion Education Social Laa Roiba Journal, 2021)
The background of this research problem is the quality of learning in Early Childhood Education (PAUD) in Bogor Regency, which still does not meet the established standards. The aims of this study are to describe: 1. PAUD policy process in improving the quality of learning, 2. Policy analysis. 3. Policy implementation, 4. Policy evaluation, 5. Barriers to policy implementation, and 6. PAUD policy implementation results. This study used a qualitative approach and data collection techniques were carried out through interviews, observations and documentation studies with data sources from the Bogor Regency Education Office in the field of PNF PAUD. The results of the research show: 1. The PAUD policy process in improving the quality of learning is based on the Regional Regulation of Bogor Regency Number 6 of 2011 in Articles 5,6,7. 2. Analysis of PAUD Policy in Bogor Regency there are still many that are not in accordance with National education standards and infrastructure facilities are not optimal, 3. Implementation of PAUD Policies, with HI (Holistic Integrative) PAUD Action Plans / Programs Partnership The Bogor Regency Education Office always synergizes and partners with organizations/institutions/associations of similar groups, 4. Evaluation of PAUD policies using accreditation as a benchmark in the quality of learning and the quality of these institutions, 5. Barriers to implementing PAUD human resource policies are constrained by the imbalance in the number of PAUD institutions with supervisors as PAUD coaches. 6. The results of the implementation of PAUD policies in improving the quality of learning, namely the implementation of Integrative Holistic PAUD as a form of service to the community in improving the quality of learning.